A Comprehensive Review of Flamelet Methods: Future Directions and Emerging Challenges - Mohammed Niyasdeen Nejaamtheen; Jeong-Yeol Choi (Energies)
Understanding and accurately modeling combustion processes in engines across a wide range of operating conditions is critical for advancing both subsonic and supersonic propulsion technologies. These engines, characterized by highly complex flow fields, varying degrees of compressibility, and intricate chemical reaction mechanisms, present unique challenges for computational combustion models. Among the various approaches, flamelet models have gained prominence due to their efficiency and intuitive nature. However, traditional flamelet models, which often assume fixed boundary conditions, face significant difficulties. This review article provides a comprehensive overview of the current state of incompressible flamelet modeling, with a focus on recent advancements and their implications for turbulent combustion simulations. The discussion extends to advanced topics such as the modeling of partially premixed combustion, the definition of reaction progress variables, efficient temperature computation, and the handling of mixture fraction variance. Despite the inherent challenges and limitations of flamelet modeling, particularly in 1D applications, the approach remains an attractive option due to its computational efficiency and applicability across a wide range of combustion scenarios. The review also highlights ongoing debates within the research community regarding the validity of the flamelet approach, particularly in high-speed flows, and suggests that while alternative methods may offer more detailed modeling, they often come with prohibitive computational costs. By synthesizing historical context, recent developments, and future directions, this article serves as a valuable resource for both novice and experienced combustion modelers.